Computational study on the influence of nozzle eccentricity in spray formation by means of Eulerian Σ - Y coupled simulations in diesel injection nozzles. (August 2020) - Salvador, F.J.; Pastor, J.M.; De la Morena, J.; Martínez-Miracle, E.C.
Highlights: The capabilities of elliptical nozzles has been assessed by means of coupled simulations of internal and external flow. The Σ- Y model is able to capture the internal geometric morphology of the nozzle and translate its characteristics to the spray. For an equal area and boundary conditions, increasing the eccentricity for horizontal elliptical nozzles improves the discharge and area coefficients due to lower cavitation. In terms of cavition, the increase of eccentricity induces a vapour field with lower intensity but more dispersed across the outlet section of the orifice. In terms of spray characteristics, more elliptic nozzles produce an improvement of air entrainment, with the minor angle showing small variations, while the major angle increases significantly. Consequently, spray penetration tends to be reduced. A significant increment of the angle and jet entrainment as the eccentricity rises are an indication that elliptical nozzles can help to improve the spray atomization processes. Abstract: The present work analyses the effect of the eccentricity of diesel nozzle orifices over the spray behaviour by means of CFD simulations. Several orifice geometries with varying horizontal eccentricity (from 0.50 to 0.94) are selected. Their performance is assessed at a high injection pressure of 200 MPa, a 3 MPa back-pressure and non-evaporative conditions. The nozzle flow characteristics, including cavitation modelled by a Homogeneous Relaxation Model (HRM), are accounted for in the spray performance by means of a Σ - Y model. The code is validated via two reference nozzles, the so called "Spray A" of the Engine Combustion Network plus a second nozzle from a production injector, and then extended to the eccentric geometries. The results and discussions include spray angle and penetration, air entrainment and flow parameters of the nozzle inner conditions versus the eccentricity value.